Adapted into multiple media: what happens when adaptations meet transmedial franchises - Camila Augusta Pires de Figueiredo (Interfaces)
Despite being two of the most popular medial phenomena in contemporary culture, few studies have been devoted to understanding what happens when adaptations meet transmedial franchises. In this study, I propose an examination of two cases in which one or more original texts have been adapted into the form of a transmedial franchise, resulting in a transmedial adaptation. The aim is to understand how transmedial adaptations transcend traditional binary models of adaptation, with one or several texts being adapted into a convergent project composed of several media. Using the examples provided, I also seek to examine how this multi-media phenomenon activates different textual and medial dynamics. In order to do so, I will use an approach that considers both intermedial and transmedial aspects of the phenomenon.